Correlation between pore size and reactivity of macro/mesoporous iron and copper hexacyanoferrates for H2O2 electrocatalysis - Gonçales, V.R. (2013)
The effect of pore size to H2O2 detection by macroporous and mesoporous Prussian blue type electrocatalysts is reported in the present paper. The macroporous electrocatalysts were prepared employing spherical colloidal particles of different sizes (300, 460, 600 and 800 nm) as sacrificial templates to synthesize a copper hexacyanoferrate/polypyrrole (CuHCNFe/Ppy) hybrid material. Surprisingly, macroporous and non-porous CuHCNFe/Ppy displayed very similar results, which led to a discussion that application of macroporous platforms in sensors must consider the material wettability and the influence of electrochemical kinetics on analyte detection. In order to evaluate the effect of smaller pores, the performance of the macroporous H2O2 sensors was also compared to electrocatalysts synthesised through the immobilization of Prussian blue and CuHCNFe layers inside the cavities of mesoporous TiO2 films with diameters of 13, 20 and 40 nm. In this scale, the results were superior than those achieved with the non-porous sensors, demonstrating the possibility of controlling the performance of H2O2 sensors according to the pore diameter and the amount of immobilized material. Among the tested porous materials, the H2O2 sensor with better performance was achieved using the 20-nm diameter TiO2 platform functionalized with Prussian blue, which presented a sensitivity of (930 ± 50) μA cm-2 mmol-1 L, detection limit of (0.49 ± 0.08) μmol L-1, response time of (6 ± 2) seconds and linear range up to (1.3 ± 0.1) mmol L-1. This performance was extremely satisfactory considering sensors operating by chronoamperometry. © 2013 Elsevier Ltd. All rights reserved.